S98 Vitamin D deficiency increases bacterial load in a murine model of sepsis-induced lung injury. (14th November 2013) - Parekh, D; Dancer, RCA; Lax, S; Perkins, GD; Thickett, DR
Abstract : Introduction: We have previously shown that patients with Acute Lung Injury (ALI) are severely vitamin D deficient. Several studies have reported a high prevalence of vitamin D deficiency in critically ill patients with sepsis, associated with increased morbidity and mortality but whether this is cause or effect is unknown. Bacteraemic sepsis is more common in the winter months when vitamin D levels are lowest. The purpose of this study was to investigate the local and systemic effects of vitamin D deficiency in a murine model of sepsis-induced lung injury where we can predictably time the initiating insult. Methods: We fed 8 wild-type C57Bl/6 mice a diet completely devoid of vitamin D for 6 weeks to induce severe vitamin D deficiency (9 nmol/l) and compared to 7 mice fed a vitamin D sufficient diet (42 nmol/l). Caecal ligation and puncture (CLP) was used to establish sepsis. Animals were culled 16h after CLP and blood, peritoneal lavage fluid (PLF) and bronchoalveloar lavage fluid (BALF) were collected. Cell infiltrates were assessed by flow cytometry. Fluid protein levels were measured and tissue protein permeability index (PPI) was calculated as the ratio between fluid and serum protein. Bacterial load was evaluated as colony-forming units (CFU) after 24h incubation on appropriate media. Results: Vitamin D deficient mice had increased bacterial load in BALF, blood and PLF compared to dietary sufficient mice. BALF protein permeability index was higher in deficient compared to sufficient mice but there was no difference in cell numbers recruited to the lung. PLF protein permeability index was also increased in the deficient group compared to sufficient mice with an associated significant increase in neutrophils recruited to the peritoneum. (See Table 1 ) Conclusion: Vitamin D deficiency significantly increases the bacterial load both systemically, locally and within the lung in a murine model of peritonitis. This is associated with an increase in tissue permeability locally and within the lung. These data support pre-existing vitamin D deficiency as a determinant of the severity of bacteraemic sepsis and may account for some of the seasonal variations observed in the incidence of sepsis.